From Academic Success to Mental Health Everything is at Cost - Teotia, Anil Kumar (JOURNAL OF INDIAN EDUCATION, 2021)
The school closure’s adverse effects are more visible on the younger children than elders, each day of school closure results in a slight loss in reading and mathematical learning outcomes. Further, school closure may delay the kids’ cognitive, social, and emotional development, and it can have a spiral impact on future developmental tasks. In this article, the researcher has tried to present various school closure and related concerns. School closure automatically means the complete absence of school tours, visits, training, and other general things. The idea of online classes seems to be unfit for Delhi’s children. This is also impacting the immigrants and first-generation children disproportionately as learning language and mathematics are limited to them. Different feelings at home were found to be nothing new—anxiety, stress, restlessness, etc. Students responded to reopen schools as soon as possible. We have to be aware of the learning loss and the potential learning crisis immediately after school reopening.